Socio-Economic Accounting and External Diseconomies. - Estes, Ralph W. (The Accounting Review, 1972)
This article presents information on socio-economic accounting. Several possible dimensions of socio-economic accounting have been suggested, including national income accounting, evaluation of social programs, the role of accounting in economic development and efforts to develop an index of social progress. This paper explores yet another dimension of socio-economic accounting-the recognition and measurement of external diseconomies, or social costs and the resulting implications for the accounting profession. The most complex and controversial, link in the assessment process is the determination of the social costs-monetizing the external diseconomies. Accountants are likely to resist involvement in such efforts because of the uncertainty involved, but such resistance is not justified. Cost determination is more the forte of accountants than of engineers and economists. Assuming that actual social cost estimation will be done by public agencies at some level of government, it then seems not unlikely that the accounting profession will be called upon to attest to such estimates.